VISIBILITY AND INTERNATIONALIZATOIN OF SOUTHERN BRAZILIAN NURSING MAGAZINE: PERSPECTIVES AND CHALLENGES - Oliveira CROSSETTI, Maria da Graça; Cammarano RIBEIRO, Aline; Oliveira de GOES, Marta Georgina (Revista Gaúcha de Enfermagem, 2013)
In recent years, there has been noteworthy movement on the part of Brazilian scientific periodicals in pursuit of visibility and internationalization. It is a subject that has been central to discussions by scientific editor forums gathering together different disciplines.(1) Among other aspects, they have been focused on how to promote the international impact of Brazilian scientific production, considering the national and international scope and relevance of the research and subsequent consumption and or application of the findings in practice. The debates are accentuated on the importance of technological development to point towards innovation as science is produced in Brazil, in such a way as to meet the population’s real needs and potential, but also on producing technology that will have a positive impact on the nation’s social and economic conditions.(2) Nevertheless, with researchers raising the alert to consider problems external to the domestic situation, aspects that will be able to give visibility to innovative technology being produced here and subsequent exportation. The magazines’ factor of impact, quality of the editors and experts or consultants, the peer review process, the difficulty of publishing in high impact periodicals, the assessment criteria used by the support agencies for classifying periodicals, the professionalization and funding of magazines are the subjects of ongoing discussions.(3,4) Led by the Brazilian Nursing Association (ABEN), Brazilian nursing scientific periodicals coparticipating in this movement have made it part of their daily agendas to call their editors into the discussion, so as to think about and introduce strategies that may solve these and other difficulties, which are great challenges for the field. The Southern Brazilian Nursing Magazine (RGE) has shown itself to be immersed in this challenging project, having promoted the production of research nurses in Brazil and Latin America without interruption since 1976. Throughout its history, it has been adapting its editorial processes, in such a way as to meet the market demands of nursing and general healthcare scientific publications, regarding managing the quality of its main product, whatever the manuscript submitted to it and its author by the confidence deposited in the RGE. Recently, RGE (Qualis B1 CAPES rating), upon request from SciELO Brasil, drew up the 2012 Annual Performance Report for the purpose of evaluating its continuance in their database. This was based on quantitative and qualitative information inherent to RGE’s nature considering the different dimensions of the editorial processes providing evidence of its progress. The work flow chart for manuscripts from their submission to acceptance and publication became more agile and skilled, in so far as the magazine created and defined attributions for submission editors (01), department editors (06) and editorial commission (04). The technical staff also became more professionalized by hiring a dedicated RGE librarian and sought community partnerships aiming towards professionalization of its editing, layout, translation and printing processes. Publication norms were revised, with a focus on the manuscript evaluation process by peer review. These findings can be added to the bibliometric indexes that identify RGE in the world of Brazilian nursing periodicals as one of those chosen by researchers to promote their production. Over the course of 2012, 1262 manuscripts were submitted. 466 of these were accepted for publication, 592 were refused and 200 were not resubmitted by their authors after requests for reformulations and/or other information, therefore being archived. The average time between manuscript submission and evaluation was 9.9 months and the average interval between acceptance and publication was 8.5 months. These metrics are in consonance with the evaluating agencies that approve a period of one year for manuscript bureaucracy from evaluation to publication. In its four fascicles, volume 33 of RGE published 81 original articles, two systematic revisions and 17 other types of productions, including theoretical revision articles and experiential reports. The 100 manuscripts published were produced by 341 authors. RGE relied on the collaboration of 259 ad hoc specialist text revisers distributed geographically across the nation. The online publication of the first translation in English, as well as in Portuguese, of volume 33, fascicle 4, in the database of SciELO Brasil is without a doubt a significant qualitative move forward for RGE, a fact that proves its ongoing commitment to promotion and visibility of Brazilian nursing’s scientific production. With this data, RGE might consider its mission to be accomplished. Nevertheless, 62.75% refusal rates for manuscripts is a great challenge to be faced, considering the example of other nursing periodicals. In the assessment process, certain weaknesses in the manuscripts are found regarding: inadequate methodological design, lack of theoretical foundation, themes of investigation irrelevant to professional practice, evidence of results and conclusions that do not contribute to the state of the art and subsequent development of knowledge specific to nursing, non-compliance with scientific writing norms and RGE’s publication norms. These are aspects that deserve to be discussed and submitted at editors’ forums together with teachers from graduate programs in nursing, far and above the ideal academic environment in which the production of clinical research assumes its essential character for nursing and as such has the responsibility to prepare young researchers in the act of consuming, producing and promoting the knowledge being produced. In a setting like this one, RGE sees itself as moving towards consolidating its visibility and internationalization beyond Latin America and is facing the challenge of contributing and continuing to seek solutions inherent to its nature, which will certainly demand great dedication and the commitment of everyone involved in making this happen. REFERENCES 1 8. Workshop de Editoração Científica: internacionalização dos periódicos científicos, 1. Seminário do COPE - Comitee on publication ethics, 3. Encontro Nacional de Bibliotecários, 6. Seminário Satélite para Editores Plenos; 2012 Nov 11-14; Florianópolis, Brasil. Florianópolis: ABEC Brasil; 2012 2 Zanetti ML. Porque é difícil publicar em periódicos de alto impacto. Rev Latinoam Enferm.2012; 20(4):633-634. 3 Erdmann AL, Marziale MHP, Pedreira MLG, Lana FCF, Pagliuca LMF, Padilha MI, et al. A avaliação de periódicos científicos Qualis e a produção brasileira de artigos da área de enfermagem. Rev Latinoam Enferm. 2009;17(3):120-127. 4 Scochi CGS, Munari DB, Pedreira MLG, Padilha ML, Marziale MH. A importância da qualificação dos periódicos para o avanço da produção e visibilidade da pesquisa em enfermagem. Texto & Contexto Enferm. 2012;21(2):251-3.